2002
DOI: 10.1152/ajpregu.00628.2001
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular and tubular responses toNG-nitro-l-arginine methyl ester are age dependent in conscious lambs

Abstract: Sener, Alp, and Francine G. Smith. Glomerular and tubular responses to N G -nitro-L-arginine methyl ester are age dependent in conscious lambs. Am J Physiol Regulatory Integrative Comp Physiol 282: R1512-R1520, 2002 10.1152/ ajpregu.00628.2001.-The present experiments were carried out to investigate the role of endogenously produced NO in modulating renal function during postnatal maturation under physiological conditions. In conscious, chronically instrumented lambs aged ϳ1 (n ϭ 8) and ϳ6 wk (n ϭ 8) of post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
28
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 38 publications
6
28
0
Order By: Relevance
“…NSAID treatment increases renal vascular resistance, reduces renal blood flow (14,30), decreases glomerular filtration rate (1,22), and is an independent risk factor for the development of acute renal failure (4). Similarly, NOS inhibition has been shown to significantly reduce renal blood flow, glomerular filtration rate, and alter tubular function in neonatal animals (27). Furthermore, a combination of a NOS inhibitor and NSAID treatment has been shown to produce significant renal side effects (such as increased serum creatinine) in human preterm neonates (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NSAID treatment increases renal vascular resistance, reduces renal blood flow (14,30), decreases glomerular filtration rate (1,22), and is an independent risk factor for the development of acute renal failure (4). Similarly, NOS inhibition has been shown to significantly reduce renal blood flow, glomerular filtration rate, and alter tubular function in neonatal animals (27). Furthermore, a combination of a NOS inhibitor and NSAID treatment has been shown to produce significant renal side effects (such as increased serum creatinine) in human preterm neonates (16).…”
Section: Discussionmentioning
confidence: 99%
“…Of particular importance, in human infants exposed in utero to NSAIDs, changes in renal morphology have been described (15,33) which are similar to the glomerulocystic changes observed in the preterm baboon kidney. NOS inhibitors elicit a similar physiological response as NSAIDS, such as reduction in renal blood flow and urine output (27); however, the effects on nephrogenesis have not been previously investigated. Therefore, the aim of this study was to determine the effects of ibuprofen treatment on renal development and morphology in the preterm baboon kidney both alone and in combination with a NOS inhibitor.…”
mentioning
confidence: 99%
“…In further support of this conjecture, it is well established that the AT 2 R functions via a nitric oxide (NO)-mediated pathway to produce cyclic GMP and increase vasodilatation (20). Certainly, there is abundant evidence in the literature that NO plays a significantly greater role in the maintenance of hemodynamic function in the neonatal vs. adult kidney, including providing protection against the vasoconstrictor effects of AngII in the newborn (21)(22)(23)(24). Furthermore, there are reports that NO production in the renal vasculature is significantly greater in the newborn vs. adult renal vasculature under normal physiological conditions (4).…”
Section: Discussionmentioning
confidence: 97%
“…Solhaug et al were the first to show an enhanced role for NO in the neonate in 1993, when intrarenal infusion of the nonspecific NOS inhibitor l-NAME into porcine caused significantly greater changes in RVR, RBF, and GFR in the newborn, than in the adult (6). This finding by Solhaug et al was confirmed in other animal models (lambs and rabbits) in which nonspecific NOS inhibition increased RVR while decreasing RBF and GFR much more significantly in neonates than in adult kidneys (4,5,8). These early studies demonstrated that the renal hemodynamics of the neonate is much more dependent on NO than that of the adult to maintain normal physiological function; however, the characteristics and exact nature of the enhanced role of NO remain unidentified.…”
Section: Discussionmentioning
confidence: 88%
“…Various studies have shown that nitric oxide (NO) plays a much more pronounced role in the neonate's hemodynamic state, as compared with the adult's, and NO counterbalances the highly activated reninangiotensin system (RAS), protecting the immature kidney from the deleterious effects of adverse perinatal events that lead to vasomotor acute renal failure (2)(3)(4)(5)(6)(7). The immature renal vasculature is highly responsive to intrarenal NO stimulation with acetylcholine and NO inhibition with the nonselective nitric oxide synthase (NOS) inhibitor L-nitro-arginine methyl ester (l-NAME) (8)(9)(10)(11), producing significantly greater increases in RVR and decreases in RBF and GFR in the immature kidney, as compared with the adult.…”
mentioning
confidence: 99%